Enhancing the Device Performance of a Blue Light-Emitting Copolymer Using CdSe/ZnS Quantum Dots - Mucur, Selin Piravadili; Lenkeit, Daniel; Kanelidis, Ioannis; San, Sait Eren; Holder, Elisabeth; Tekin, Emine (Wiley, 2014)
An alternating triarylamine-functionalized fluorene-based copolymer synthesized using a Suzuki-Miyaura cross-coupling procedure is used as blue emitting layer in polymer light-emitting diodes (PLEDs). Subsequently, the effects of CdSe/ZnS quantum dots (QDs) on the optoelectronic properties of the copolymer are investigated. Therefore, CdSe/ZnS QDs are embedded into the copolymer matrix and hybrid PLEDs are fabricated. The devices comprised of CdSe/ZnS QDs reveal enhanced performances, yielding about 3.4 times more luminous efficiency than that of the device without QDs. Further enhancement is achieved by using electron transport layer; the luminous efficiency rose from 0.065 to 1.740 cd A(-1) for the hybrid PLEDs, corresponding to a superb 27-fold intensification of the efficiency. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 147-156
Keywords: conjugated polymers; luminescence; morphology; nanocomposites; thin films